Pengetahuan Keluarga Dengan Perilaku Pencegahan Penularan Tuberkulosis Paru di Puskesmas Sumurgung Kecamatan Palang - Ariyana, Khofifah Novi; Nugraheni, Wahyuningsih Triana; Ningsih, Wahyu Tri (Peneliti.net, 2024)
Tuberculosis in Indonesia is one of the most common diseases, although Indonesia still has a high rate of pulmonary TB. Lack of awareness of pulmonary TB sufferers and their families is one of the causes of the disease. The aim is to determine the relationship between knowledge and behavior to prevent transmission of pulmonary tuberculosis at the Sumurgung Community Health Center, Palang District. Collaborative analytic research design with a cross-sectional approach. The research population of all families of pulmonary tuberculosis patients in 2022 at the Sumurgung Community Health Center was 51 people. The sampling technique used is total sampling. The sample from this study was 51 families of pulmonary tuberculosis patients. Independent variable is family knowledge, dependent variable is family behavior in preventing pulmonary tuberculosis. How to collect data with a questionnaire, using the